The measure of each equilateral triangle is 60°.
Given that, in an equilateral triangle, all side lengths are equal and all angle measures are equal.
Isosceles triangles are those triangles that have at least two sides of equal measure. The side opposite the vertex angle is called the base and base angles are equal.
The sketch of equilateral triangle is given below:
The measure of each equilateral triangle is 60°.
The sketch of isosceles triangle is given below:
Two different possibilities for the angle measures of an isosceles triangle are 45°, 45° and 90°.
Another triangle has 65°, 65° and 50°.
Therefore, the measure of each equilateral triangle is 60°.
To learn more about an equilateral triangle visit:
#SPJ5
I know this isn’t a answer or a step by step explanation but can someone please help and explained this it’s so confusing and hard
y ≥ 0
y > 2
y ≥ 2
The range of the function f(x) : is y > 0.
The correct option is (A)
The definition of range is the set of all possible values that the function will give when we give in the domain as input.
Given function is :
If we draw the graph for this, then we can see that the horizontal asymptote is 0.
So, the range is real numbers higher than 0.
Hence, the range should be y > 0.
Learn more about this concept here:
#SPJ2
∠1 and ∠5 ?
corresponding angles
adjacent angles
alternate interior angles
alternate exterior angles
2x^2+5x-9=0
The quadratic equation 2x^2+5x-9 = 0 has two solutions or zeros, which may be real or complex. They can be found using the quadratic formula: x = [-5 + sqrt(97)]/4 and x = [-5 - sqrt(97)]/4.
The equation given is 2x^2+5x-9=0, which is a quadratic equation. The solutions or zeros of a quadratic equation can be found using the quadratic formula: x = [-b ± sqrt(b^2 - 4ac)]/2a. Here, a=2, b=5, and c=-9.
Let's substitute these values into the formula:
x = [-(5) ± sqrt((5)^2 - 4*2*(-9))]/2*2
x = [-5 ± sqrt(25 + 72)]/4
x = [-5 ± sqrt(97)]/4
Therefore, this equation has "two solutions" or zeros, which are x = [-5 + sqrt(97)]/4 and x = [-5 - sqrt(97)]/4.
#SPJ2
A. y - 7 = 4 ( x - 3 )
B. y - 7 = 4 ( x + 3 )
C. y + 7 = 4 ( x + 3)
D. y + 7 = 4x - 12
Answer:
The equation of this line is y - 7 = 4(x + 3)
Step-by-step explanation:
To find this, start with the base form of point-slope form.
y - y1 = m(x - x1)
Now put the slope in for m and the two coordinates in for (x1, y1).
y - 7 = 4(x + 3)